(untitled) (Journal of Informatics Education and Research, 2024)
In 2024, the integration of Artificial Intelligence (AI) and Machine Learning (ML) into portfolio management has revolutionized investment strategies, offering new avenues for optimizing returns and managing risks. This paper investigates the application of AI-enhanced portfolio management, focusing on how machine learning algorithms are leveraged to analyze vast datasets, identify patterns, and predict market trends with unprecedented accuracy. The study explores various AI-driven techniques, such as reinforcement learning, natural language processing, and sentiment analysis, which are used to develop dynamic and adaptive investment strategies. These advanced methods enable the continuous adjustment of portfolios in response to real-time market conditions, enhancing the ability to achieve optimal asset allocation and risk diversification. Additionally, the paper examines the ethical considerations and potential biases inherent in AI models, emphasizing the importance of transparency and regulatory oversight in AI-driven financial decision-making. Through case studies and empirical analysis, this research highlights the transformative potential of AI in portfolio management, offering insights into the future of investment strategies and the evolving role of financial professionals in an AI-dominated landscape.